Smaller baseline subcortical infarct volume predicts good outcomes in patients with a large core in early acute ischemic stroke after endovascular treatment - Gu, Yiming; Ding, Yasuo; Hang, Yu; Cao, Yuezhou; Jia, Zhenyu; Zhao, Linbo; Liu, Ying; Liu, Sheng (Frontiers in Neuroscience, 2023)
Background:Patients with acute ischemic stroke (AIS) and a large core may benefit from endovascular treatment (EVT) in the early time window. Purpose:To examine the prognostic factors for good outcomes in patients with a large core (70 - 130 ml) after EVT. Material and Methods:We retrospectively reviewed 40 patients who met the criteria from October 2019 to April 2021. Based on the modified Rankin Score (mRS) at 90 days, the patients were divided into a good outcome group (mRS 0-2) and a poor outcome group (mRS 3-6). Baseline and procedural characteristics were collected for unilateral and multivariate regression analyses to explore the factors that influence good outcomes. In particular, the infarct territories were quantified as subcortical infarct volume (SIV) and cortical infarct volume (CIV). Results:Of the 40 patients included, good outcomes were observed in 11 (27.5%) patients. Younger age, smaller SIV and larger mismatch volume were noted in the good outcome group than in the poor outcome group (all P < 0.05). Multivariate logistic regression analysis showed that only a smaller SIV (odds ratio [OR] 0.801; 95% CI 0.644 - 0.996; P = 0.046) was an independent predictor for good outcomes. The receiver operating characteristic curve indicated a moderate value of SIV for predicting good outcomes, with an area under the receiver operating characteristic curve of 0.735 (95% CI 0.572 - 0.862; P = 0.007). Conclusion:SIV was an independent predictor of good outcomes in patients with a large core after EVT in the early time window.